Comparative analysis of sex-dependent serum metabolomic patterns across the lifespan of rhesus macaques - Metzler, Ludwig A. P.; Goy, Robinson W.; Metzger, Jeanette M.; Emborg, Marina E.; Kapoor, Amita (Frontiers in Genetics, 2025)
IntroductionAging is accompanied by systemic metabolic changes that contribute to disease susceptibility and functional decline. Sex differences in aging have been reported in humans, yet their mechanistic basis remains poorly understood. Due to their physiological similarity to humans, rhesus macaques are a powerful translational model to investigate sex-specific metabolomic aging under controlled conditions.MethodsTargeted serum metabolomics were conducted in 58 rhesus (35 females, 23 males), ranging from 1.66 to 25.71 years of age, quantifying 513 metabolites spanning lipids, amino acids, and related compounds. Multivariate, univariate, and generalized additive model (GAM) analyses were performed to evaluate age-associated trajectories and test for sex differences.ResultsAge-related changes in both sexes were identified in metabolites related to hormones (e.g., DHEAS), amino acid biosynthesis and catabolism (e.g., beta-alanine, sarcosine, t4-OH-pro), and energy metabolism (e.g., hexose). Sex affected age-related metabolic trajectories in lipids, amino acids and related compounds, and gut microbial species. Females demonstrated a profound increase in serum triglycerides (TGs), amino acids, and other small molecules, while males exhibited a heterogenous profile with changes in lipids, but no TGs were affected. Males also exhibited altered levels of amino acids and related metabolites, hormones, gut microbial metabolites, and energy-associated metabolites.ConclusionThese results highlight pronounced sex differences in metabolomic aging trajectories in rhesus macaques, particularly in lipid and amino acid metabolism. These findings underscore the importance of incorporating sex as a biological variable in aging studies and support the utility of rhesus macaques for identifying conserved, sex-specific biomarkers of biological aging.